Lattice Boltzmann Study of Flow and Temperature Structures of Non-Isothermal Laminar Impinging Streams (Communications in Computational Physics, 2020)
Previous works on impinging streams mainly focused on the structures offlow field, but paid less attention to the structures of temperature field, which are veryimportant in practical applications. In this paper, the influences of the Reynolds number (Re) and Prandtl number (Pr) on the structures of flow and temperature fieldsof non-isothermal laminar impinging streams are both studied numerically with thelattice Boltzmann method, and two cases with and without buoyancy effect are considered. Numerical results show that the structures are quite different in these cases.Moreover, in the case with buoyancy effect, some new deflection and periodic structures are found, and their independence on the outlet boundary condition is also verified. These findings may help to understand the flow and temperature structures ofnon-isothermal impinging streams further.